Propuesta didáctica de iniciación a la gimnasia rítmica para mejorar la coordinación motora gruesa en niños de 3 años, 2018 - Blas Gutiérrez, Teresa (2019)
The present research considers that the Introduction to the Rhythmic Gymnastics, as a strategy, improving gross motor coordination in children of 3 years old and other aspects such as their muscle tone and flexibility. Likewise, the objective is to inform theoretical aspects on the rhythmic gymnastics and gross motor coordination; in addition to the theoretically analyze the relationship among them and with this, we can consolidate activities to be performed and above all, activities that can do the children of this age._x000D_ The proposal has as main purpose help many teachers, mothers and people of concern to provide a solution to the problematic situation which present or may present their children in relation to a lacking, little or poor gross motor coordination in their body; because of that it has been considered activities to be used as intervention strategies._x000D_ For the development of work will use methods such as: analysis of documents and registration documentary to collect all possible information that serves as a basis for the elaboration of this proposal teaching._x000D_ Is very important that all teachers know the subject of the research because their intervention will prevent future difficulties of coordination and deficiencies in children´s bodies